Early versus late MRI in asphyxiated newborns treated with hypothermia. Issue 1 (5th August 2010) - Wintermark, Pia; Hansen, Anne; Soul, Janet; Labrecque, Michelle; Robertson, Richard L; Warfield, Simon K
Abstract : Objective: The purposes of this feasibility study were to assess: (1) the potential utility of early brain MRI in asphyxiated newborns treated with hypothermia; (2) whether early MRI predicts later brain injury observed in these newborns after hypothermia has been completed; and (3) whether early MRI indicators of brain injury in these newborns represent reversible changes. Patients and methods: All consecutive asphyxiated term newborns meeting the criteria for therapeutic hypothermia were enrolled prospectively. Each newborn underwent one or two early MRI scans while receiving hypothermia, on day of life (DOL) 1 and DOL 2–3 and also one or two late MRI scans on DOL 8–13 and at 1 month of age. Results: 37 MRI scans were obtained in 12 asphyxiated neonates treated with induced hypothermia. Four newborns developed MRI evidence of brain injury, already visible on early MRI scans. The remaining eight newborns did not develop significant MRI evidence of brain injury on any of the MRI scans. In addition, two patients displayed unexpected findings on early MRIs, leading to early termination of hypothermia treatment. Conclusions: MRI scans obtained on DOL 2–3 during hypothermia seem to predict later brain injuries in asphyxiated newborns. Brain injuries identified during this early time appear to represent irreversible changes. Early MRI scans might also be useful to demonstrate unexpected findings not related to hypoxic–ischaemic encephalopathy, which could potentially be exacerbated by induced hypothermia. Additional studies with larger numbers of patients will be useful to confirm these results.